2018
DOI: 10.1002/smtd.201800018
|View full text |Cite
|
Sign up to set email alerts
|

Stable Hydrogen Production from Water on an NIR‐Responsive Photocathode under Harsh Conditions

Abstract: Photoelectrochemical (PEC) water splitting using a cell composed of a photocathode and photoanode is an attractive approach to producing hydrogen utilizing solar energy. Photocathodes based on nonoxide materials exhibit high solar‐to‐hydrogen conversion efficiencies thanks to their narrow bandgaps. However, the corrosion of photocathode surfaces at oxidative potentials and under highly alkaline conditions has resulted in insufficient durability. Here, the PEC properties of near‐infrared‐sensitive (ZnSe)0.85(Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
(97 reference statements)
0
25
0
Order By: Relevance
“…In this work, the ZnSe : CIGS particles were synthesized by a flux method [18][19] and subsequently used to fabricate a photo- [20] (see Figure S1 in the Supporting Information (SI)). After appropriate surface modifications, [15,17,[21][22] a commercially-available TiO 2 nanoparticle suspension (Solaronix, Ti-Nanoxide HT-L/SC) was drop cast onto the photocathode surface and dried in air, followed by the PEC deposition of Pt. [8,18,19] The resulting assemblies, consisting of photocatalytic particles and a metal layer obtained by the PT method and subsequent surface modifications, were hot pressed with commercially-available membrane filters together with anionic ionomers to prepare MPAs for MCH production.…”
Section: ð1þmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the ZnSe : CIGS particles were synthesized by a flux method [18][19] and subsequently used to fabricate a photo- [20] (see Figure S1 in the Supporting Information (SI)). After appropriate surface modifications, [15,17,[21][22] a commercially-available TiO 2 nanoparticle suspension (Solaronix, Ti-Nanoxide HT-L/SC) was drop cast onto the photocathode surface and dried in air, followed by the PEC deposition of Pt. [8,18,19] The resulting assemblies, consisting of photocatalytic particles and a metal layer obtained by the PT method and subsequent surface modifications, were hot pressed with commercially-available membrane filters together with anionic ionomers to prepare MPAs for MCH production.…”
Section: ð1þmentioning
confidence: 99%
“…This is confirmed by the two dimensional Fourier transform in Figure 3b. Based on the EDS data in Table 1, the Pt particles are imaged in the annular dark field (ADF)-STEM image of the Pt/ We have previously reported that surface modification of a ZnSe : CIGS photocathode with RuO 2 can increase the resistance of the cathode to highly alkaline electrolytes, [22] and that the utilization of such alkaline conditions can promote selective MCH production due to the improved performance of the anion exchange membrane. [8] On this basis, a ZnSe : CIGS MPA modified with both RuO 2 and Pt/TiO 2 was evaluated for PEC MCH production in the present work (Figure 4, in which "RuO 2 / Pt/RuO 2 " indicates co-loading with Pt and RuO 2 as previously reported), with using the MPA structure where the photocathode facing to the strong alkaline electrolyte phase.…”
Section: ð1þmentioning
confidence: 99%
“…Rather, the suppression of the anodic dark current by the thick TiO 2 layer implies mitigated migration of holes toward the photocathode‐electrolyte interface due to deep valence band position of TiO 2 . One possible reason for the instability of such CdS‐modified photocathodes is the photocorrosion of CdS caused by backward migration of holes to the photocathode‐electrolyte interface . Indeed, the ZnSe : CIGS photocathode without TiO 2 modification showed obvious anodic photoresponse at more positive potential than 0.8 V RHE , possibly resulted in photocorrosion of CdS, whereas the TiO 2 ‐modified ZnSe : CIGS photocathode showed cathodic photoresponse at all potential range up to 1.0 V RHE (see Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…[15] This was done because a ZnSe:CIGS photocathode modified sequentially with CdS, In 2 S 3 , and RuO 2 layers is capable of driving PEC hydrogen evolution from highly alkaline water in a stable manner. [16] The details regarding preparation of the photocathode are provided in the SI. The cathodic photocurrent generated by the ZnSe:CIGS photocathode was found to be halved when it was placed under a semitransparent Mg-modified Ta 3 N 5 /CNT photoanode (Figure 4a).…”
Section: A Semitransparent Nitride Photoanode Responsive Up To λ = 60mentioning
confidence: 99%